(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
A National Security Law has officially come into force in Spain, establishing a National Security System and contributing to international security. Its key components are National Defence, Public Security and External Action. With a view to improving the necessary anticipation, prevention, analysis of, reaction and resistance to, as well as the recovery from risks and threats that might compromise National Security, the proposal is presented here for a new cross-cutting dimension not specifically contemplated heretofore, which is the Security of Land Routes and the Security of Mobility and Land Transport, and for Spain to assume a leading role in the EU Commissariat for Security Union.